The economic effects of COVID-19 in Sweden: A report on income, taxes, distribution, and government support policies - Nikolay Angelov; Daniel Waldenström (Institute of Labor Economics (IZA), 2023)
This report analyses the economic consequences of the coronavirus pandemic and support policies using underutilized data sources from the Swedish Tax Agency's tax register, which provides real-time information on firm sales and employees' wage income. Firms' sales, particularly in areas heavily impacted by COVID-19, declined by 6.1% on average, inducing a drastic economic recession. Excise tax revenue analysis reveals a decline in industrial electricity and air travel tax revenues, but a rise in alcohol tax revenue. The hospitality industry experienced significant negative effects, with drops in sales, employment, and wage income. Payroll tax revenues decreased due to government intervention, whereas sick pay drastically increased. Average pre-tax labor income decreased by 5%, largely due to increased unemployment among part-time workers, escalating income inequality. Policy simulations indicate government support measures mitigated wage income reduction and unemployment rise, yet they contributed to income inequality under certain conditions. These results provide insight into the diverse, yet significant, economic impacts of the pandemic. A number of policy recommendations are presented based on the empirical findings.
Keywords: D31; H12; H24; J22; J24; 330; COVID-19; taxes; inequality; policy effects